Sexual function recovery after robot‐assisted radical prostatectomy: Outcomes from an Italian referral centre and predicting nomogram. (18th August 2019) - Cozzi, Gabriele; Musi, Gennaro; Monturano, Massimo; Bagnardi, Vincenzo; Frassoni, Samuele; Jereczek‐Fossa, Barbara A.; Ferro, Matteo; Bianchi, Roberto; Mistretta, Francesco A.; de Cobelli, Ottavio
Abstract: Aims of this study were to assess sexual recovery after robotic‐assisted radical prostatectomy (RARP) and to build a nomogram predicting 1‐year sexual function. From May 2015 to July 2016, all patients eligible for RARP at our institution were invited to enter the study. The Expanded Prostate cancer Index Composite (EPIC) questionnaire was administered pre‐operatively, then at 45 days, and at 3, 6, 9, and 12 months post‐operatively. According to sexual function scores, patients were divided into four classes. Multivariate analysis was used to investigate the influence of patient‐ and disease‐related features on sexual recovery. A total of 643 patients were included. Age was associated with baseline potency ( p < .0001). Bioptic Gleason score (GS; p = .0002), American Society of Anesthesiologists (ASA) score ( = .002ASA Physical Status Classification System ) and Charlson Comorbidity Index (CCI; p = .02) were negatively associated with potency. Baseline sexual function was associated with potency recovery. A nomogram resulted from fitting a proportional odds logistic model for ordinal outcomes, with 1‐year sexual function as a dependent variable and baseline sexual potency, age, body mass index (BMI), clinical stage, biopsy GS, initial prostate‐specific antigen (iPSA), ASA score, and CCI as predictors. After further validation, this nomogram could be a useful tool for the pre‐operative counselling.